2014
DOI: 10.1097/inf.0000000000000020
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Transmission of Mumps in a Highly Vaccinated Population in Orange County, NY, 2009–2010

Abstract: Two doses of mumps-containing vaccine may not be as effective in outbreak settings with multiple, prolonged and intense exposure. Additional studies are required to understand why such mumps outbreaks occur and how they can be prevented in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…Similar studies also reported that mumps outbreaks among highly vaccinated populations tended to occur in highdensity settings such as universities and schools, with teenagers as the most vulnerable group. 8,10,[14][15][16]18,19 These findings indicate that among highly vaccinated populations, despite herd immunity, intense exposures to one or more mumps cases may increase the risk of transmission, even in the most recently vaccinated children. It is possible that such risk factors may overcome vaccine-induced immunity resulting in persistence of transmission of the disease.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Similar studies also reported that mumps outbreaks among highly vaccinated populations tended to occur in highdensity settings such as universities and schools, with teenagers as the most vulnerable group. 8,10,[14][15][16]18,19 These findings indicate that among highly vaccinated populations, despite herd immunity, intense exposures to one or more mumps cases may increase the risk of transmission, even in the most recently vaccinated children. It is possible that such risk factors may overcome vaccine-induced immunity resulting in persistence of transmission of the disease.…”
Section: Discussionmentioning
confidence: 87%
“…[12][13][14][15][16] Between October 2012 and March 2013, 148 cases of mumps were notified in the Central Region of Portugal to the Regional Health Administration. In contrast, there was no evidence of outbreaks elsewhere in the country between 2009 and 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the OC village, the larger household size in general and high-density settings such as schools may have resulted in transmission of mumps. 27 In previously reported studies crowded educational settings such as schools, universities, and camps, have played an important role in transmission of mumps. 5,[28][29][30][31][32][33] No evidence has suggested that other factors such as handling changes and vaccine lots were risk factors for vaccine failure.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks among unvaccinated groups are easily explained, but, interestingly, there have been several reports of outbreaks among highly immunized groups (1)(2)(3)(4), some of which included cases of patients previously immunized with two doses of the measles-mumps-rubella (MMR) vaccine (2,(4)(5)(6)(7)(8). In light of the high efficacy of the MMR vaccine against mumps, the reason for these outbreaks is unclear.…”
mentioning
confidence: 99%